Phosphorylase-cross-reactive antibodies evoked by streptococcal M protein. - Dale, J B (1990)
Rabbit antisera evoked by type 5 streptococcal M protein (M5) were screened by enzyme-linked immunosorbent assay (ELISA) for immunological cross-reactivity with purified rabbit muscle phosphorylases a and b. Of 10 pep M5 antisera tested, 3 showed significant cross-reactivity with both forms of the enzyme. ELISA inhibition studies using one of the pep M5 antisera showed that all of the phosphorylase b antibodies were inhibited by pep M5, the immunogen, and phosphorylase b, the ELISA antigen. All of the antibodies were also inhibited by pep M6 and pep M19, but not by pep M24, indicating that the cross-reactive epitopes were shared by multiple serotypes of M protein. Western blot (immunoblot) analyses showed that pep M5 antisera reacted strongly with the subunit of phosphorylase b. In addition, purified phosphorylase partially inhibited the binding of pep M5 antibodies to a 95-kilodalton protein of human myocardium. One of the three cross-reactive pep M5 antisera inhibited the enzymatic activity of phosphorylase a in a dose-related fashion, reaching a maximum inhibition of 75%. The enzymatic activity in the presence of antibody was totally restored when the antiserum was first incubated with pep M5.